Commentary: Vulnerable children—A global perspective. Issue 183 (6th May 2022) - Bulat, Jennae; Gove, Amber
Abstract: In this commentary, we discuss the global similarities in the intersections of poverty, disability, and learning, and share lessons that are being learned internationally that can inform U.S. domestic research and implementation. These lessons cover multiple aspects of learning and development, instructional materials and approaches, integration of social emotional and school climate considerations, and engagement of families and communities.